2021
DOI: 10.3390/biology10111123
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Prospects for Nanotechnology in Wheat Biofortification

Abstract: The deficiency of nutrients in food crops is a major issue affecting the health of human beings, mainly in underdeveloped areas. Despite the development in the methods of food fortification, several barriers such as lack of proper regulations and smaller public-private partnerships hinder its successful implementation in society. Consequently, genetic and agronomic biofortification has been suggested as the potential techniques for fortifying the nutrients in diets. However, the time-consuming nature and restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 97 publications
1
12
0
Order By: Relevance
“…This positive finding required positive modulations in RWC, MSI, PhPiC, LSPC, and LSAnF, along with further improvements in OPrSC, TrigC, AsA, GSH, AAc, PhCC, and FlaC, which were already achieved through foliar nourishment with nP ( Table 3 , Table 4 , Table 5 , Table 6 , Table 7 , Table 8 , Table 9 and Table 10 ). These results are consistent with those obtained previously [ 10 , 16 , 24 , 37 , 39 , 46 , 47 , 69 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This positive finding required positive modulations in RWC, MSI, PhPiC, LSPC, and LSAnF, along with further improvements in OPrSC, TrigC, AsA, GSH, AAc, PhCC, and FlaC, which were already achieved through foliar nourishment with nP ( Table 3 , Table 4 , Table 5 , Table 6 , Table 7 , Table 8 , Table 9 and Table 10 ). These results are consistent with those obtained previously [ 10 , 16 , 24 , 37 , 39 , 46 , 47 , 69 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Discussionsupporting
confidence: 94%
“…The use of nanophosphorus (nP) has remarkable enhancing effects on plant growth and production by improving physio-biochemical indices and antioxidant defense strategies as a result of relieving abiotic stress. Foliar nourishment with nP noticeably improves growth, yields, leaf chlorophyll, photosynthetic efficiency, membrane stability index, relative water content, various antioxidant activities, P content, and various osmo-regulatory compounds in Phaseolus vulgaris and Triticum aestivum plants [ 24 , 46 ]. Since P is an essential component of amino acids, high-energy molecules (ADP and ATP), nucleic acids, and phospholipids in plants [ 47 ], it is, therefore, a pivotal nutrient essential for plant growth, development, and reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…NFs may help to moderate the adverse impacts of synthetic fertilizers (Rajput et al, 2021a ) with the added advantage to compensate nutritional deficiencies to allow the plants to develop normally (Bernal et al, 2007 ; Baloch et al, 2008 ), as shown in Supplementary Table 1 . The nutrient shortage in soils may pose threat to soil profile by lowering nutritional elements for agricultural crops (Khan et al, 2021 ). Fertilizers are used in large amounts to boost agricultural yield, although more macronutrients are unavailable to plants (Zulfiqar et al, 2019 ).…”
Section: Nutritional Imbalancementioning
confidence: 99%
“…Recently, nano-technology has also been explored for micronutrient biofortification in wheat. Khan et al ( 41 ) have extensively reviewed the status of nano formulation-based wheat biofortification with a critical analysis of its merits and demerits.…”
Section: Introductionmentioning
confidence: 99%